One Dimensional Site Response Analysis of Liquefaction Potential along Coastal Area of Bengkulu City, Indonesia - Lindung Zalbuin Mase (Civil Engineering Dimension, 2018)
This paper presents one dimensional non-linear site response analysis of liquefaction potential caused by the 2000 and the 2007 earthquakes in coastal area of Bengkulu City, Bengkulu, Indonesia. Site investigations, including Standard Penetration Test (SPT) and shear wave velocity (VS) measurement, were conducted in three locations along the coastal area of Bengkulu City. Further, the site investigation data were used in simulation of one-dimensional non-linear site response analysis by applying the synthetic ground motions at bedrock. The results show that liquefaction could happen at 0 to 1.5 m deep. This was indicated by the excess pore water pressure ratio (ru) which exceeded one. At depth between 1.5 m and 20 m, the excess pore water pressure almost reached the initial effective stress decreasing the effective confinement pressure close to zero. The results also indicated that liquefaction is possible to occur in this depth range if a stronger earthquake occurs.